Virtual Reality and Three-Dimensional Printed Models Improve the Morphological Understanding in Learning Mandibular Sagittal Split Ramus Osteotomy: A Randomized Controlled Study - Zhang, Henglei; He, Yu; Chen, Ying; Liu, Jianfeng; Jin, Qi; Xu, Shixing; Fu, Xi; Qiao, Jia; Yu, Bing; Niu, Feng (Frontiers in Surgery, 2021)
Background: The mandibular sagittal split ramus osteotomy (SSRO) is a routine operation performed to correct mandibular deformity including mandibular retrusion, protrusion, deficiency, and asymmetry. The SSRO remains a challenging procedure for junior surgeons due to a lack of adequate morphological knowledge necessary for success in clinical practice. Virtual reality (VR) and three-dimensional printed (3DP) models have been widely applied in anatomy education. The present randomized, controlled study was performed to evaluate the effect of traditional educational instruments, VR models, and 3DP models on junior surgeons learning the morphological information required to perform SSRO. Methods: Eighty-one participants were randomly assigned to three learning groups: Control, VR, and 3DP. Objective and subjective tests were used to evaluate the learning effectiveness of each learning instrument. In the objective test, participants were asked to identify ten anatomical landmarks on normal and deformed models, draw the osteotomy line, and determine the description of SSRO. In the subjective test, participants were asked to provide feedback regarding their subjective feelings about the learning instrument used in their group. Results: The objective test results showed that the VR and 3DP groups achieved better accuracy in drawing the osteotomy line (p=0.027) and determining the description of SSRO (p=0.023) than the Control group. However, there was no significant difference among the three groups regarding the identification of anatomical landmarks. The VR and 3DP groups gave satisfactory subjective feedback about the usefulness in learning, good presentation, and enjoyment. The Control and 3DP groups reported positive feelings about ease of use. Conclusion: The current findings suggest that VR and 3DP models were effective instruments that assisted in the morphological understanding of SSRO-related anatomical structures. Furthermore, 3DP models may be a promising supplementary instrument to bridge the gap between conventional learning and clinical practice.